Legal Void of Social and Environmental Responsibility in the Implementation of Corporate Social Responsibility in the Energy and Natural Resources Sector - Suhadi Sukendar Situmorang; Boy Nurdin (Journal of Social Research, 2024)
This research aims to explore the legal vacuum related to Social and Environmental Responsibility (CSR) in the implementation of Corporate Social Responsibility (CSR) in the energy and natural resources sector. Although CSR has been recognized as an important aspect of sustainability and corporate responsibility, the regulation regarding the minimum amount of funds that must be allocated for CSR is still not clearly and concretely regulated in the applicable legislation in Indonesia. The results show that legal uncertainty regarding the amount of TJSL funds has a significant impact on the implementation of CSR programs by companies. Many companies experience difficulties in planning and allocating budgets for effective CSR programs, due to the absence of clear guidelines regarding the funding obligations that must be met. The study also identified various challenges faced by companies in implementing CSR, including differences in understanding of CSR among stakeholders, environmental challenges arising from operational activities, and community pressure to increase social and environmental contributions.